The effects of pharmacological treatment of ADHD on children's health - Søren Dalsgaard; Helena Skyt Nielsen; Marianne Simonsen (Institute for the Study of Labor (IZA), 2012)
We are the first to investigate longer-term effects of pharmacological treatment of ADHD on children's health. We rely on a difference-in-differences strategy while exploiting Danish register-based panel data for children born in 1990-1999. We study effects of treatment initiated between ages five and ten and document that treated children benefit in terms of fewer hospital contacts in general, fewer emergency ward contacts, and fewer injuries. Estimated effects are large: early treatment is effective in reducing the probability of at least one hospital contact in a given year with around 30% compared to the mean. Effects are significantly smaller in later cohorts where more children are diagnosed and treated.
Keywords: I1; 330; ADHD; evaluation; health; Kinder; Psychische Störung; Pharmazeutisches Produkt; Bewertung; Dänemark